Effects of postpartum anxiety disorders and depression on maternal self-confidence - Reck, Corinna; Noe, Daniela; Gerstenlauer, Jakob; Stehle, Eva (Infant behavior and development, 2012)
Low maternal self-confidence may damage the early mother-infant relationship and negatively influence infant development. The goal of this study was to test whether a current and previous history of DSM-IV anxiety and depressive disorders is associated with maternal self-confidence two weeks after delivery. Postpartum anxiety disorder and depression was diagnosed according to DSM-IV criteria in a community sample of 798 women. The data showed a significant link between current postpartum anxiety and depressive disorders and maternal self-confidence. Furthermore, women with a depression or anxiety disorder in their previous psychiatric history scored lower in maternal self-confidence. There is a need for appropriate preventive programmes to promote maternal self-confidence. With such programmes it is possible to prevent infant developmental disorders which might result from reduced feelings of maternal self-confidence and associated maternal interaction behaviour.
Gesehen am 23.04.2018